INTRODUCING ABOVE GROUND STORAGE TANK (AST) TO HELP JUNIOR HIGH SCHOOL STUDENTS UNDERSTAND FLUID PRESSURE - Suwarma, Irma Rahma; Haryanti, Anti; Kaniawati, Ida (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Fluid pressure is considered as an abstract concept so that an innovative method must be used to help the students understand it correctly. We introduced Above Ground Storage Tank (AST) to the students to help them grasp the fundamentals of fluid pressure and evaluated how this approach improved their scientific communication ability. Based on their ability in communicating the mechanism of fluid pressure, students were able to organize their knowledge, delivering their knowledge to other people, and making a better conclusion after the introduction of AST. Thus, it can be concluded that the introduction of AST can improve students’ scientific communication ability.